The Implementation of the Sexual Violence Crime Law in Educational Settings: A Victimological Perspective - Hartanto, Hartanto; Putri, Nur Anita Owiwanti (fakultas hukum universitas PGRI Semarang, 2026)
This study examines the legal protection available to victims of sexual violence within educational institutions, viewed through a victimological perspective in the implementation of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). Sexual violence in educational environments remains a serious issue, with cases like “H.W” tragedy highlighting the inadequacy of institutions in providing safe spaces for students. Victims often suffer from psychological trauma, social stigma, and barriers to justice. This research employs a normative legal approach with qualitative methods to analyze the law’s application. Findings show that UU TPKS includes victimological principles, such as compensation, assistance, and rehabilitation for victims. However, its implementation faces structural and cultural challenges, such as power imbalances and victim-blaming. Effective protection requires institutional commitment, cultural transformation, and active engagement from the academic community to establish comprehensive and sustainable systems of support for victims